Reforms In The Activity Of Mahallas (Neighborhood) In Uzbekistan (Zien Journal of Social Sciences and Humanities, 2024)
In this article examines ways to enhance the effectiveness of the activities of the Mahalla Citizens' Assemblies and investigates the primary aspects of changes occurring within them. The study substantiates the need to strengthen the financial foundations of Mahalla assemblies, introduce transparent mechanisms for the utilization of Mahalla budgets, and implement information and communication technologies along with mechanisms for public oversight